Stability analysis of rice (Oryza satiya)-Wheat (Triticum aestivum) cropping system in integrated nutrient management - KATYAL, V; SHARMA, S K; GANGWAR, K S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted on integrated nutrient supply system.in rice (Oryza sativa L.)-wheat (Triticumaestivuw L.emend, Fiori & Paol.) cropping sequence at 5 centres since 1983-91 showed that 50% recommended NPk+50% through crop residue in rice followep. by 100% NPK in wheat could stabilize yields of rice and wheat at Kanpur.whereas 50% N need of rice can be substituted by farmyard manure, followed by 100% NPK in wheat at Ludhiana, AtJabalpur the 50% recommended NPK + 50% through green-manuring could stabilize yields of both the crops, whereasat Masodha, yields of rice and wheat were stabilized when 50% recommended NPK was used in conjunction with 50%recommended crop residues, At Kalyani, 75% recommended NPK + 25% by green-manuring in rainy (kharif) seasonfollowed by 75% recommended NPK in winter (rabi) season could stabilize yields of rice and wheat and save 25% Nfertilizer in winter season. The continuous rice-wheat cropping increased the organic carbon status at Masodha andKanpur increased whereas it remained same at Jablapur, It also increased available P and K at Masodha and KanpurHowever, at Jabalpur decreasted in available P and increase in K was observed. Integrated nutrient supply had favourableeffect on' organic carbon status and available P and K at all the centres except P at Jablapur.